Cognitive Frame and Time Pressure as Moderators Of Clinical Reasoning: A Case Control Study - Andrew J. Monick; Xiao Chi Zhang (Western Journal of Emergency Medicine)
Introduction: Emergency physicians (EP) are uniquely positioned to benefit from a deeper understanding of cognitive bias, particularly in the context of limited processing time. The framing effect—the tendency to evaluate identical information inconsistently given varying methods of presentation— presents a particular challenge within emergency medicine (EM). Understanding how the presentation of clinical information affects medical decision-making is paramount, given variability in how information is received. In this study we aimed to assess whether the imposition of a cognitive frame and time pressure affected participants’ differential diagnoses. Methods: We recruited attending physicians in emergency medicine (EM) and third-year EM residents via email from our university hospital. They were asked to review two case vignettes: one consistent with pulmonary embolism (PE), the other with interstitial lung disease. Each vignette had two versions, one emphasizing features consistent with the respective diagnoses. Each pair of vignettes contained objectively identical clinical information. Subjects were randomly assigned to one of four conditions based on 1) the specific or non-specific-frame version of each case and 2) the inclusion or exclusion of time pressure. Subjects provided their top three differential diagnoses for each case. Our primary outcome measure was identification of intended diagnosis. Results: A total of 39 subjects completed the study. Two-sided Fisher exact tests showed that varying cognitive frames affected the likelihood of EPs identifying PE as a diagnosis of interest ( P = .01). Among EPs who identified PE, the likelihood of this diagnosis leading their differential diagnosis was also related to frame ( P = .01). Conclusion: The results of this work reveal that cognitive frame and time pressure may independently influence diagnostic reasoning among emergency physicians, bearing implications for medical education.